Pengaruh Kegiatan Ekstrakurikuler Terhadap Kualitas Hasil Belajar Siswa SMP N 20 Medan - Amanda, Suci Ade; Napitupulu, Fazriah Aulia; Putri, Ridha Hasanah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research discusses the influence of extracurricular activities on the quality of learning outcomes for students at SMP Negeri 20 Medan. This research is quantitative research where data is collected in the form of a questionnaire, and processed in the form of percentages (%) and analyzed using statistical analysis techniques. The total population was 342 students selected using purposive sampling of 25 samples. The research results show that there is a positive influence between extracurricular activities and the quality of student learning outcomes of 0.791 and is in the correlation coefficient which is included in the very low category. This means that both influence each other. This means that if students are more active in extracurricular activities, their learning achievements will increase. .